Cross-Border Framework for Effective Presentation to Investment Committees across Multiple Jurisdictions - Blessing Olajumoke Farounbi,; Chizoba Michael Okafor,; Esther Ebunoluwa Oguntegbe, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
Globalization of capital markets has intensified the need for investment committees to evaluate opportunities across multiple jurisdictions, each with distinct regulatory, cultural, and economic contexts. This develops a cross-border framework for effective presentation to investment committees, aimed at enhancing comparability, transparency, and decision-making efficiency in multi-jurisdictional environments. The framework addresses key challenges such as fragmented disclosure standards, heterogeneous risk perceptions, and jurisdiction-specific legal and governance requirements. The proposed approach is built on three core principles: clarity, comparability, and adaptability. Clarity is achieved through standardized financial metrics, explicit assumptions, and transparent documentation of methodologies. Comparability is enhanced by benchmarking opportunities against both global and local peers, ensuring that investment committees can evaluate relative performance across geographies. Adaptability ensures that presentations are tailored to regulatory environments and cultural decision-making norms, while maintaining consistency with overarching institutional strategies. The framework integrates multiple layers of analysis. A regulatory and compliance layer ensures adherence to both domestic mandates and international best practices such as IFRS, ISSB, and Basel standards. A financial and risk analytics layer captures macroeconomic trajectories, capital structures, sectoral opportunities, and scenario-based stress tests across diverse jurisdictions. ESG integration further strengthens the framework by embedding sustainability metrics and governance indicators aligned with international disclosure norms. Finally, technology-enabled tools—such as collaborative cloud platforms, real-time dashboards, and AI-driven analytics—facilitate cross-border consistency, transparency, and efficiency. This argues that adopting a harmonized yet adaptable presentation framework enhances investor confidence, reduces regulatory fragmentation, and improves the resilience of decision-making processes. By combining financial rigor, regulatory alignment, and technological innovation, the framework provides investment committees with a robust, forward-looking tool to navigate the complexities of global capital allocation.
Keywords: Cross-Border Framework; Investment Committee Presentation; Multi-Jurisdictional Compliance; Global Governance; Regulatory Alignment; Risk Disclosure; Financial Reporting Standards; Strategic Communication; Stakeholder Engagement; Due Diligence Integration; Decision-Making Support; Portfolio Transparency; Legal Structuring